Macroeconomic Adjustment with Segmented Labor Markets - Aizenman, Joshua (IMF Working Papers; Working Paper ;, 1994)
This paper analyzes the macroeconomic effects of fiscal and labor market policies in developing countries. The basic framework considers a small open economy with a large informal production sector and a heterogeneous work force. The labor market is segmented as a result of efficiency considerations and minimum wage laws. The basic model is then extended to account for unemployment benefits, income taxation, and imperfect labor mobility across sectors. The analysis indicates, among other results, that a reduction in unemployement benefits has a positive effect on output of tradable goods by lowering both the level of efficiency wages and the relative rent captured by skilled workers.